2016
DOI: 10.1007/s00247-016-3634-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior urethral valves: are neonatal imaging findings predictive of renal function during early childhood?

Abstract: Presence of cortical hyperechogenicity, cystic changes or bilateral reflux cannot be considered prognostic of renal failure by the age of 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
2
0
5
Order By: Relevance
“…Such heterogeneity likely also contributes to difficulties in identifying factors predictive of renal outcomes. Small studies have inconsistently shown association of antenatal diagnosis, prematurity, oligohydramnios, renal parenchymal changes, nadir creatinine, vesicoureteral reflux, bladder dysfunction, and younger age at diagnosis with worse renal outcomes; however in multivariate analyses only nadir creatinine has been predictive [4][5][6][7][8][9][10][11][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…Such heterogeneity likely also contributes to difficulties in identifying factors predictive of renal outcomes. Small studies have inconsistently shown association of antenatal diagnosis, prematurity, oligohydramnios, renal parenchymal changes, nadir creatinine, vesicoureteral reflux, bladder dysfunction, and younger age at diagnosis with worse renal outcomes; however in multivariate analyses only nadir creatinine has been predictive [4][5][6][7][8][9][10][11][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…Заболеваемость УК у мальчиков, по разным данным, составляет от 1:5000 до 1:8000 случаев [1]. Диагностика основывается на сборе анамнеза, жалоб, объективном осмотре, выполнении ультразвукового исследования, уретроцистографии, урофлоуметрии и уретроцистоскопии [2][3][4][5]. В большинстве случаев диагноз удается установить на первом году жизни ребенка [6].…”
Section: Introductionunclassified
“…[1][2][3][4] Apesar da mortalidade ter diminuído, as VUP continuam a ser uma importante causa de morbilidade, 5 evoluindo para doença renal crónica (DRC) em aproximadamente 30% dos casos, com DRC terminal em cerca de 25% na puberdade. 4,[6][7][8] Cada vez mais o diagnóstico das VUP é sugerido no período pré-natal através de ecografia obstétrica, geralmente no segundo ou terceiro trimestres de gestação. 1,7 Esta pode revelar dilatação do trato urinário superior, alterações parenquimatosas renais, como córtex hiperecogénico, ausência de diferenciação córtico-medular (DCM) e diminuição da espessura cortical, espessamento parietal vesical (> 3 mm) e oligohidrâmnios, o qual pode provocar hipoplasia pulmonar e deformidades esqueléticas.…”
Section: Introductionunclassified
“…1,7 Esta pode revelar dilatação do trato urinário superior, alterações parenquimatosas renais, como córtex hiperecogénico, ausência de diferenciação córtico-medular (DCM) e diminuição da espessura cortical, espessamento parietal vesical (> 3 mm) e oligohidrâmnios, o qual pode provocar hipoplasia pulmonar e deformidades esqueléticas. 1,6 Raramente pode ocorrer rotura vesical com ascite ou formação de urinoma perirrenal. 1 Contudo, em alguns casos, o diagnóstico só ocorre no período pós-natal durante a investigação de pielonefrite aguda (PNA) grave ou de repetição, de alterações do jato urinário, ou perante quadros de incontinência, enurese ou retenção urinária.…”
Section: Introductionunclassified
See 1 more Smart Citation